PERBANDINGAN HASIL BELAJAR SISWA DENGAN METODE INDEX CARD MATCH DAN BAMBOO DANCING - Moli Novela; Amrul Bahar; Hermansyah Amir (University of Bengkulu, 2017)
[COMPARISON OF STUDENT LEARNING OUTCOMES BEETWEN INDEX CARD MATCH AND BAMBOO DANCING LEARNING METHOD] In the learning process teachers often use lecture methods so that students tend to only accept what is given by teachers and many students who feel chemistry lessons are difficult and confusing lessons. This results in low student learning outcomes. One effort that can be done by using the teacher method is varied, one of which is the method of Index Card Match and Bamboo Dancing. This research type is experiment. The population is all students in class X MIPA SMA Negeri 2 Kota Bengkulu as many as 216 students. The sample selection was done by homogeneity test with the result obtained by class X MIPA C (experimental class I) which applied Index Card Match method and X MIPA D (experiment II class) applying Bamboo Dancing method. Data analysis used is normality test, homogeneity test and t test. In this study the results of learning are seen the value of the difference between the average pretest and posttest, where obtained for class X MIPA C is 53.75 and class X MIPA D is 45.55. Then t test is obtained where t test t > t table (3,76 > 2,38), so it can be concluded that there is a significant difference between student learning result using Index Card Match method with Bamboo Dancing on chemical compound nomenclature material.